Wojciech Szczepiński (1924–2010), Obituary - Petryk, H.; Editorial Board, the (Archives of Mechanics, 2010)
Professor Wojciech Szczepiński, member of the Editorial Advisory Board and former long-term member of the Editorial Committee of Archives of Mechanics, passed away on June 6th, 2010.